Analisa Kebijakan Pemerintah Republik Indonesia terhadap Pemberlakuan Mutual Recognition Agreement (MRA) di Negara-Negara Anggota ASEAN - Rika Isnarti; Wiwiek Rukmi Dwi Astuti; Poppy Irawan (TRANSBORDERS: International Relations Journal, 2021)
This paper analyzes the Indonesian government's response to the implementation of the Mutual Recognation Agreement implemented by ASEAN. high number of unskilled workers, the high competition of work, and the lack of employment for local residents, will make the MRA a challenge for Indonesia. Instead of getting benefits, Indonesia can experience overwhelm between the number of professional workers from outside and the use of local workers. whereas, Indonesian unskilled workers are unable to compete at the ASEAN level. This paper uses a qualitative method by collecting documents in a library research. This paper found that Indonesia has high number workforce, but the proportion of non-skilled workers is greater than skilled workers. In order to face the competition of skilled foreign workers in response to the MRA, the Indonesian government has prepared an increase in the quality of education and the implementation of qualifications and efforts to raise awareness of this situation to the community. However, this effort has not been able to run well due to differences in the level of qualifications between education owned by Indonesia and the unequal distribution of related institutions to make efforts to improve the quality of Indonesian workers in all regions of Indonesia